p38 MAPK activation and H3K4 trimethylation is decreased by lactate in vitro and high intensity resistance training in human skeletal muscle - Willkomm, L.; Gehlert, S.; Jacko, D.; Schiffer, T.; Bloch, W. (PLOS ONE, 2017)
Exercise induces adaptation of skeletal muscle by acutely modulating intracellular signaling, gene expression, protein turnover and myogenic activation of skeletal muscle stem cells (Satellite cells, SCs). Lactate (La)-induced metabolic stimulation alone has been shown to modify SC proliferation and differentiation. Although the mechanistic basis remains elusive, it was demonstrated that La affects signaling via p38 mitogen activated protein kinase (p38 MAPK) which might contribute to trimethylation of histone 3 lysine 4 (H3K4me3) known to regulate satellite cell proliferation and differentiation. We investigated the effects of La on p38 MAPK and H3K4me3 in a model of activated SCs. Differentiating C2C12 myoblasts were treated with La (20 mM) and samples analysed using qRT-PCR, immunofluorescence, and western blotting. We determined a reduction of p38 MAPK phosphorylation, decreased H3K4me3 and reduced expression of Myf5, myogenin, and myosin heavy chain (MHC) leading to decreased differentiation of La-treated C2C12 cells after 5 days of repeated La treatment. We further investigated whether this regulatory pathway would be affected in human skeletal muscle by the application of two different resistance exercise regimes (RE) associated with distinct metabolic demands and blood La accumulation. Muscle biopsies were obtained 15, 30 min, 1, 4, and 24 h post exercise after moderate intensity RE (STD) vs. high intensity RE (HIT). Consistent with in vitro results, reduced p38 phosphorylation and blunted H3K4me3 were also observed upon metabolically demanding HIT RE in human skeletal muscle. Our data provide evidence that La-accumulation acutely affects p38 MAPK signaling, gene expression and thereby cell differentiation and adaptation in vitro, and likely in vivo.